Reduced gas seepages in ophiolitic complexes: Evidences for multiple origins of the H2-CH4-N2 gas mixtures. (15th February 2018) - Vacquand, Christèle; Deville, Eric; Beaumont, Valérie; Guyot, François; Sissmann, Olivier; Pillot, Daniel; Arcilla, Carlo; Prinzhofer, Alain
Highlights: Gas generation during serpentinization. Deep origin of nitrogen seepages in obducted ophiolitic complexes. Multiple sources of gas and gas mixing in ophiolitic complexes. Multiple sources of carbon during abiotic methane generation. Abstract: This paper proposes a comparative study of reduced gas seepages occurring in ultrabasic to basic rocks outcropping in ophiolitic complexes based on the study of seepages from Oman, the Philippines, Turkey and New Caledonia. This study is based on analyses of the gas chemical composition, noble gases contents, stable isotopes of carbon, hydrogen and nitrogen. These seepages are mostly made of mixtures of three main components which are H2, CH4 and N2 in various proportions. The relative contents of the three main gas components show 4 distinct types of gas mixtures (H2 -rich, N2 -rich, N2 -H2 -CH4 and H2 -CH4 ). These types are interpreted as reflecting different zones of gas generation within or below the ophiolitic complexes. In the H2 -rich type, associated noble gases display signatures close to the value of air. In addition to the atmospheric component, mantle and crustal contributions are present in the N2 -rich, N2 -H2 -CH4 and H2 -CH4 types. H2 -bearing gases are either associated with ultra-basic (pH 10–12) spring waters or they seep directly in fracture systems from the ophiolitic rocks. In ophiolitic contexts, ultrabasic rocks provide an adequate environment with available Fe 2+ and alkaline conditions that favor H2 production. CH4 is produced either directly by reaction of dissolved CO2 with basic-ultrabasic rocks during the serpentinization process or in a second step by H2 -CO2 interaction. H2 is present in the gas when no more carbon is available in the system to generate CH4 . The N2 -rich type is notably associated with relatively high contents of crustal 4 He and in this gas type N2 is interpreted as issued mainly from sediments located below the ophiolitic units.